The effect of employee workplace representation on firm performance: A cross-country comparison within Europe - Annette van den Berg; Yolanda K. Grift; Arjen van Witteloostuijn; C. Boone; O. van der Brempt (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2013)
In this paper, we contribute to the extant Industrial Relations literature, which is almost completely confined to estimating the effects of worker participation within a single country, by conducting a comparative multi-country study using unique data from the European Company Survey 2009. We compare representation regimes within the European Union. We categorize the EU Member States into five clusters with similar participation characteristics: the Germanic, French, Anglo-Saxon, Scandinavian and transition cluster. Across these clusters, we first estimate the effects of the presence of what we refer to as an information and consultation body on firm performance, measured by economic performance of the establishment as assessed by managers-respondents. Second, we estimate the effects of managerial attitudes on performance, as we assume – and find – that only taking into account the mere presence of a worker representation is insufficient, as mutual understandings between management and employee representatives affect the functioning of the employee representation body, and hence firm performance.
Keywords: 330; employee representation; works councils; firm performance; international comparison; Europe; ECS2009